Пошаговое объяснение:
1)-4+3у=1-2у
3y + 2y = 1 + 4
5y=5
y=1
2) 5-3b=b+8
-3b-b = 8 -5
-4b=3
b=-3/4 = -0.75
3)7k-3=2k +7
7k - 2k = 7 +3
5k=10
k=5
4)5*(2 +a)-7=a+15
10+5a-7-a=15
4a=15-10+7
4a=12
a=3
1) -4+3у=1-2у
2y+3y=1+4
y=5:5
-b-3b=-5+8
b=3:(-4)
b=-0,75
3) 7k-3=2k+7
7k-2k=3+7
k=10:5
k=2
4) 5*(2 +a)-7=a+15
10+5a-7=a+15
-a+5a=-10+7+15
a=12:4
Пошаговое объяснение:
1)-4+3у=1-2у
3y + 2y = 1 + 4
5y=5
y=1
2) 5-3b=b+8
-3b-b = 8 -5
-4b=3
b=-3/4 = -0.75
3)7k-3=2k +7
7k - 2k = 7 +3
5k=10
k=5
4)5*(2 +a)-7=a+15
10+5a-7-a=15
4a=15-10+7
4a=12
a=3
Пошаговое объяснение:
1) -4+3у=1-2у
2y+3y=1+4
5y=5
y=5:5
y=1
2) 5-3b=b+8
-b-3b=-5+8
-4b=3
b=3:(-4)
b=-0,75
3) 7k-3=2k+7
7k-2k=3+7
5k=10
k=10:5
k=2
4) 5*(2 +a)-7=a+15
10+5a-7=a+15
-a+5a=-10+7+15
4a=12
a=12:4
a=3